Harnessing Emotional Connections to Improve Financial Decisions : Evaluating the Impact of Financial Education through Mainstream Media - Berg, Gunhild (World Bank, Washington, DC, 2015)
Financial education is important, yet there is a considerable knowledge gap in how best to deliver it. The literature on careful evaluations of financial literacy is small but growing, and has moved away from classroom based interventions to more innovative delivery mechanisms such as videos and DVDs. Yet, the scope and reach of even the best produced DVDs is limited on the supply side, and attracting viewership can be significantly challenging on the demand side. As emotional connections are established between a show and its audience, the program provides a potentially powerful platform for communicating messages and influencing behavior. There is considerable evidence, especially in the health and education fields, on the success of media campaigns in improving social behavior. In this brief the authors evaluate financial education through a popular television soap opera in South Africa, scandal. The authors study the effectiveness of these messages through three quantitative surveys and three qualitative focus groups, with the former providing insight on the mechanism of measured impacts. This brief illustrates the benefits of complementing quantitative analysis with qualitative work to better understand mechanisms behind measured impacts.